Analisis Komparatif Efektivitas Implementasi Kurikulum Merdeka Dalam Meningkatkan Kesadaran Sejarah Siswa di SMA Negeri 11 Muaro Jambi - Okta Fitri Astuti; Fardan Mahobi; Ahmad Alamin Putra; Muhammad Kaafii (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the effectiveness of the implementation of the Merdeka Curriculum in improving students’ historical awareness at SMA Negeri 11 Muaro Jambi. The study is motivated by the importance of history learning in shaping national identity, national character, and students’ critical thinking skills amid the development of modern education. The research employed a descriptive qualitative method with data collection techniques conducted through interviews with history teachers and several students at SMA Negeri 11 Muaro Jambi. The data were analyzed through data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the implementation of the Merdeka Curriculum has a positive impact on improving students’ historical awareness. More flexible, interactive, and project-based learning encourages students to actively understand historical materials and relate historical events to present-day life. In addition, the use of discussion methods and exploration of historical sources was considered effective in increasing students’ learning interest. However, several obstacles were found, including limited learning time and students’ adaptation to the new learning system. Based on the findings, it can be concluded that the Merdeka Curriculum is sufficiently effective in improving students’ historical awareness at SMA Negeri 11 Muaro Jambi.